Memetakan Budaya dalam Analisis Ruang: Memahami Ruang Komunal pada Masyarakat Madura dengan Space Syntax - Santoso, Dian Kartika; Setyabudi, Irawan (TRANSFORM: Journal of Tropical Architecture and Sustainable Urban Science, 2025)
Tanean Lanjhang is a traditional communal space of the Madurese community that embodies social, cultural, and kinship values through its distinctive spatial configuration. This study aims to understand how the spatial arrangement of Tanean Lanjhang supports social interaction and preserves cultural identity using a Space Syntax analysis approach. The research method integrates field surveys, spatial mapping with GIS, syntactic analysis using DepthmapX, and qualitative interviews with local communities. The findings reveal that the central open space of Tanean Lanjhang exhibits high levels of integration and connectivity, serving as a hub for communal activities and reinforcing social cohesion. Meanwhile, private areas surrounding the courtyard show high control values, reflecting the social hierarchy within the extended Madurese family. The study also explores how adaptation to modernization alters spatial configurations while retaining core cultural values. These findings emphasize the importance of incorporating local wisdom into contemporary spatial planning and expand the application of Space Syntax to the study of traditional cultures.